Collection development practice in Indian Institute of Technology libraries of Eastern India: a study. (1st April 2019) - Gulnaz,; Fatima, Nishat
Abstract : Purpose: The purpose of this paper is to present the situation of collection development and management of Indian Institute of Technology (IIT) Guwahati and IIT Patna libraries. This research includes other areas of collection development, i.e. collection development policy, acquisition of resources, selection of resources and budget allocation. The collection management includes accessibility, stock verification, shelf arrangement, weeding out and library security of IIT Guwahati and IIT Patna Central Libraries. Design/methodology/approach: A structured questionnaire was sent to the librarians via e-mail, which includes 20 questions with 103 preferences. Findings: Present research has found that there is a difference in newly established IIT Patna library and old IIT Guwahati library in some aspects of collection development. In the library of IIT Patna, library committee is responsible for collection development policy as well as recommender of resource selection, whereas in IIT Guwahati library advisory committee is responsible for collection development policy and selection of resources on the recommendation of faculty members. The IIT Patna library is not facing any problem, while IIT Guwahati library facing many problems i.e., lack of funds, information explosion and literature scattered. The RFID is used in IIT Patna library, while in IIT Guwahati library it is under process. Research limitations/implications: The study is limited to the collection development policies undertaken in IIT Patna and IIT Guwahati in eastern India. The research questions are limited to the theme only. Therefore, the findings of the study are not valid for an in-depth study. Practical implications: The study has great importance for librarians of IITs which have recently established in India. The findings and suggestions can serve as groundwork and could help to solve some common problems that had been faced by them. Originality/value: This is a comparative study of IIT Guwahati and IIT Patna libraries in eastern India. The collection development aspects, i.e. selection, acquisition, finance and collection management, play a vital role in the collection development to serve their users. The study can serve as a base for future studies in other academic and special libraries.